Pengaruh Peer Group Terhadap Perilaku Kekerasan Pada Siswa SMA Tirtonirmolo Bantul - Margono Margono; Eko Suryani (Poltekkes Kemenkes Yogyakarta, 2017)
Adolescence is a transitional period, where adolescents feel doubts about the role that must be done. One of the problems that oftenarise in adolescence is the act of mischief. This study aims to determine the influence of Peer Group against Violence Behavior inSMA Tirtonirmolo Bantul. This type of research is an analytic research. The research design used Quasi experiment method pre testposttest design without control group. The sampling technique used is purposive sampling with the sample number 80 respondents.Data analysis using Wilcoxon. The results showed that most respondents experienced a decrease in verbal violence behavior aftergetting information from Peer Group that is equal to 58.8%. Based on the results of data analysis with Wilcoxon Signed Rank it isknown that, there is a significant difference (meaningless) statistically with t test p = 0.000 (p <0.05). The conclusion of the researchshows the influence of Peer Group on Violence Behavior in SMA Tirtonirmolo Bantul.